RANCANG BANGUN SISTEM INFORMASI PARIWISATA SULAWESI SELATAN BERBASIS ANDROID DENGAN MENGGUNAKAN METODE PROTOTYPING - musdar, izmy alwiah; Arfandy, Hamdan (SINTECH (Science and Information Technology) Journal, 2020)
Abstract Tourism is one of the sectors that has the opportunity to become the largest contributor to foreign exchange in Indonesia. Indonesia's tourism growth was recorded at 7.2 percent per year, higher than the average world tourism growth of 4.7 percent. The availability of information that is easy and fast to access can make people know about tourism in the Province of South Sulawesi so that it is expected to have an impact on increasing tourist arrivals. In this study, a tourism information system for mobile Sulawesi Province has been developed. The information system was developed by utilizing the prototyping model. The result of this research is a mobile-based tourism information system that is able to present tourism information such as tourist destinations, culinary tours, events, and photos of tourism objects. Tourism information system can be run on Android devices. The developed system can present tourism information which includes 110 destinations, 39 events, 45 culinaries, and photos of tourist attractions from 12 regions. The result of system testing was the features of the system can function properly and successfully show tourism information.